18 Traumatic cardiac arrest: is survival possible?. (26th April 2019) - Camacho, C; Mancho, G; Pastor, E; Garcia-Ochoa, MJ; Corral, E
Abstract : Background: Survival in traumatic PCR has been considered almost impossible, so it was even question whether it was indicated to perform CPR. Nowadays, several studies publish variable survival rates but they are a reality. Aim: To analyze the survival of patients suffering from traumatic CRP treated by an emergency service. Method: Observational study of patients suffered from traumatic cardiac arrest in 2016, 2017 and 2018 assisted by our EMS. Collection data from medical records and databases of hospital follow-ups. Scope: City of Madrid. Data processing and data analysis: quantitative variables are described by central and dispersion measures and qualitative variables by frequent distribution. Excel and SPSS v.20.0. Results: 303 cardiac arrest of traumatic origin were selected, of which CPR is performed in 155 (51.2%). Of these, CPR was abandoned for futility in 43 (27.74%). Rest of patient were 112 (with complete CPR), 49 (43.75%) recovered the spontaneous circulation. After 6 hours, 33 patients were alive (29.46%). After 24 hours 16.96% and after 7 days 7.14%. Conclusion: Survival in traumatic cardiac arrest is possible, 7.14% of patients are alive after 7 days. - Our survival rates are comparable to those of other series published in the scientific journals. – It's possible that survival will improve in the next years due to the new management of TCA. Conflict of interest: There is no conflict of interest. Funding: There is no funding.